Diagnostic Delay and Its Predictors in Cluster Headache - Kim, Byung-Su; Chung, Pil-Wook; Kim, Byung-Kun; Lee, Mi Ji; Chu, Min Kyung; Ahn, Jin-Young; Bae, Dae Woong; Song, Tae-Jin; Sohn, Jong-Hee; Oh, Kyungmi; Kim, Daeyoung; Kim, Jae-Moon; et al. (Frontiers in Neurology, 2022)
Objective Cluster headache (CH) is a rare, distinctive primary headache disorder, unlike other primary headaches. Given the debilitating nature of CH, delayed diagnosis can increase the disease burden. Thus, we aimed to investigate the diagnostic delay, its predictors, and clinical influence among patients with CH. Methods Data from a prospective multicenter CH registry over a 4-year period were analyzed. CH was diagnosed according to the International Classification of Headache Disorders (ICHD)-3 criteria, and diagnostic delay of CH was assessed as the time interval between the year of the first onset and the year of CH diagnosis. Patients were classified into three groups according to the tertiles of diagnostic delay (1st tertile, <1 year; 2nd tertile, 1–6 years; and 3rd tertile, ≥7 years). Results Overall, 445 patients were evaluated. The mean duration of diagnosis delay was 5.7 ± 6.7 years, (range, 0 to 36 years). Regarding age of onset, majority of young patients (age <20 years) belonged to the third tertile (60%), while minority of old patients (>40 years) belonged to the third tertile (9.0%). For year of onset, the proportion of patients in the 3rd tertile was the highest for the groups before the publication year of the ICHD-2 (74.7%) and the lowest for the groups after the publication year of the ICHD-3 beta version (0.5%). Compared with the first CH, episodic CH (multivariable-adjusted odds ratio [aOR]=5.91, 95% confidence intervals [CI]=2.42–14.48), chronic CH (aOR=8.87, 95% CI=2.66–29.51), and probable CH (aOR=4.12, 95% CI=1.48–11.43) were associated with the tertiles of diagnostic delay. Age of onset (aOR=0.97, 95% CI=0.95–0.99) and PHQ-9 score (aOR=0.96, 95% CI=0.93–0.99) were inversely associated with the tertile of diagnostic delay. The mean HIT-6 score increased significantly with the diagnostic delay (P = 0.041). Conclusions Patients with a younger onset of CH have a higher risk of diagnostic delay. Nevertheless, the rate of delayed diagnosis gradually improved over time and with the publication of the ICHD crtiteria, supporting the clinical significance of diagnostic clinical criteria and headache education to reduce the disease burden of CH.